PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS CERITA FABEL SISWA KELAS VIII SMP NEGERI 3 BUKITTINGGI - Yuliani, Adela Sari; Atmazaki, Atmazaki; Basri, Irfani (Universitas Negeri Padang, 2020)
ABSTRACTÂ This research aims to describe the effect of using mind mapping technique to writing skill the fable story text student in grade VIII SMP Negeri 3 Bukittinggi. This research data is a score in the skills of writing the story fable text not with and by using mind mapping techniques. The type of this research is quantitative research done using experiment design. The results of this study are the skill of writing fable story text students in grade VIII SMP Negeri 3 Bukittinggi not by using mind mapping technique stay in qualification more than enough (LdC) and the skill of writing the fable story text students in grade VIII SMP Negeri 3 Bukittinggi by using mind mapping technique is qualification good (B). Based on t-test concluded that the use of technic mind mapping influence the skill of writing the fable story text because ttabel<thitung (1,70<2,74).Â Kata kunci: Pengaruh, TeknikÂ Mind Mapping, Teks Cerita Fabel